Mechanical properties of PVC-based wood–plastic composites effected by temperature - Li, Jile; Huo, Ruili; Liu, Wenyi; Fang, Hai; Jiang, Lei; Zhou, Ding (Frontiers in Materials, 2022)
Compared with traditional wooden building materials, polyvinyl chloride (PVC)-based wood–plastic composites have advantages of good weather resistance, easy processing capability, energy conservation, and environmental protection and have been popular and widely used in the field of civil construction and garden engineering in recent years. Due to the difference in the thermal expansion coefficient between its component materials, the stress will accumulate in the wood–plastic composites (WPCs) when the temperature changes, which will affect the mechanical properties of the material and structure. In order to explore the changes in mechanical properties of WPCs under different temperatures and achieve a safe and controllable design, the differential scanning calorimetry (DSC) method was used in this study to measure the glass transition temperature of the WPC between 78.45°C and 88.30°C, and the glass transition temperature (Tg) was about 83.54°C. The tensile, compressive, and bending mechanical property tests of PVC-based wood–plastic composite materials under different temperatures were carried out in the ambient temperature chamber to obtain the failure characteristics, the load–displacement curve, and the influence of temperature on their mechanical properties.